Efektifitas Iklan Negatif Di Media Sosial Dalam Politik Di Indonesia - Rully Rully (LONTAR: Jurnal Ilmu Komunikasi, 2018)
Political advertising has been part in series of political campaigns with all its dynamics. Interestingly, social media is quite effective attracting voters thus emerging the supporting community. This phenomenon is felt since 2014 Elections, when viewed furthermore, the shared content in socmed has same patterns packing political ads, which plays negative issue in society.Â How is the effectiveness of political ads through socmed in Indonesian politics? Why is a negative political ads tends to have more influence in society? According Perloff (2014), the feature of political ads is to direct its negativity, used for colorful roles in presidential campaigns and proving that it is easier for people to consider negative advertising than positive advertising.Qualitative descriptive analysis will reveal the phenomena with relevant theories to the effects of socmed illustrating its power to form partisan.